2012
DOI: 10.1155/2012/693124
|View full text |Cite
|
Sign up to set email alerts
|

Combined Posterior and Anterior Ankle Arthroscopy

Abstract: Treatment of combined anterior and posterior ankle pathology usually consists of either combined anterior and posterior arthrotomies or anterior ankle arthroscopy with an additional posterolateral portal. The first technique bears the risk of complications associated with the extensive exposure, the latter technique provides limited access to the posterior ankle joint. A case is described of combined anterior and posterior arthroscopy, with the patient lying prone and then turned supine, addressing both anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…We did not observe a higher rate of infections in our patients, which is in accordance with the data reported by other authors using this approach. 1,3,41 A study of a technique in which anterior ankle arthroscopy was performed first, followed by position switching from supine to prone, reported that the median time needed for position switching was 15 minutes. 28 However, patients were under general anesthesia, the leg was initially positioned in a holder with the hip flexed for 45 degrees, and with the use of noninvasive bandage distraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not observe a higher rate of infections in our patients, which is in accordance with the data reported by other authors using this approach. 1,3,41 A study of a technique in which anterior ankle arthroscopy was performed first, followed by position switching from supine to prone, reported that the median time needed for position switching was 15 minutes. 28 However, patients were under general anesthesia, the leg was initially positioned in a holder with the hip flexed for 45 degrees, and with the use of noninvasive bandage distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors used a different approach, performing a posterior ankle arthroscopy in a prone position initially, followed by a position switching to supine, and anterior ankle arthroscopy. 1,3,41 The described technique was used in our study as well. Patients had spinal anesthesia, positioned without the use of a holder, and under no distraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reposition of the patient was necessary during the operation. 14 They performed the arthroscopic debridement of the posterior ankle with the patient in prone position and then carried out repeated prep and drape to perform the arthroscopic debridement of the anterior ankle with the patient in the supine position. Wound healing complications were significantly reduced, whereas the posteromedial approach resulted in a higher risk of neurovascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of combined anterior and posterior ankle pathology usually requires either a combined anterior and posterior arthrotomies or anterior ankle arthroscopy with an additional posterolateral portal. The first technique bears the risk of complications associated with extensive exposure while the latter provides limited access to the posterior ankle joint [ 8 ].…”
Section: Introductionmentioning
confidence: 99%